The photoplethysmography dictionary: practical guidance on signal interpretation and clinical scenarios from TeleCheck-AF. (14th October 2021) - Van Der Velden, R M J; Verhaert, D V M; Hermans, A N L; Gawalko, M; Duncker, D; Manninger, M; Hemels, M; Pisters, R; Lodzinski, P; Steven, D; Sultan, A; Crijns, H J G M; et al.
Abstract: Introduction: During the coronavirus disease 2019 (COVID-19) pandemic, numerous centres in Europe used on-demand photoplethysmography (PPG) technology to remotely assess heart rate and rhythm in conjunction with teleconsultations within the TeleCheck-AF project. Purpose: To develop an educational structured stepwise practical guide on how to interpret PPG signals and to study typical clinical scenarios how on-demand PPG was used in the TeleCheck-AF project. Methods: During an online conference, the structured stepwise practical guide on how to interpret PPG signals was discussed and further refined during an internal review process. We provide the number of respective PPG recordings and number of patients managed within a clinical scenario during the TeleCheck-AF project. Results: To interpret PPG recordings, we introduce a structured stepwise practical guide and provide representative PPG recordings. In the TeleCheck-AF project, 2522 subjects collected 90.616 recordings. The majority of these recordings was classified by the PPG algorithm as sinus rhythm (57.6%), followed by atrial fibrillation (AF) (23.6%). In 9.7% of recordings the quality was too low to interpret. Other observed rhythms were tachycardia (1.4%), extra systoles (4.7%), bigeminy episodes (1.8%), trigeminy episodes (0.6%) and atrial flutter (0.2%). The most frequent clinical scenario where PPG technology was used in the TeleCheck-AF project was follow-up after AF ablation (1110 patients) followed by heart rate and rhythm assessment around (tele)consultation (966 patients), sometimes including remote PPG-guided adaption of rate or rhythm control. 275 patients were followed around cardioversion, either (semi-)acute or elective. Other possible scenarios are assessment of palpitations, assessment of symptom-rhythm correlation and monitoring during up-titration of heart failure medication. Conclusion: We introduce a newly developed structured stepwise practical guide on PPG signal interpretation developed based on presented experiences from TeleCheck-AF. The present clinical scenarios for the use of on-demand PPG technology derived from the TeleCheck-AF project will help to implement PPG technology in the management of arrhythmia patients. Funding Acknowledgement: Type of funding sources: None.